Stochastic forward-backward-half forward splitting algorithm with variance reduction - Qin, Liqian; Zhang, Yaxuan; Dong, Qiao-Li; Rassias, Michael Th (Optimization letters, 2025)
In this paper, we present a stochastic forward-backward-half forward splitting algorithm with variance reduction for solving the structured monotone inclusion problem composed of a maximally monotone operator, a maximally monotone operator and a cocoercive operator in a separable real Hilbert space. By defining a Lyapunov function, we establish the weak almost sure convergence of the proposed algorithm, and obtain the linear convergence when one of the maximally monotone operators is strongly monotone. Numerical examples are provided to show the performance of the proposed algorithm.